2003
DOI: 10.1590/s0034-72992003000500014
|View full text |Cite
|
Sign up to set email alerts
|

Emissões otoacústicas - produto de distorção em indivíduos expostos ao chumbo e ao ruído

Abstract: At ualmente, as legislações nacionais voltadas à saúde do trabalhador exigem que a audição seja monitorada apenas quando há exposição ocupacional ao ruído, não sendo considerada, assim, a exposição a produtos químicos. Entretanto, na literatura científica, é bastante clara a preocupação sobre os efeitos do chumbo no sistema auditivo, uma vez que foram observados efeitos negativos após a exposição ocupacional a este metal. Objetivo: O presente estudo teve como objetivo analisar a amplitude das emissões otoacúst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
2
12
0
6
Order By: Relevance
“…In this study, the children subjected to evoked otoacoustic emissions through transient stimulus research presented normal result, bilaterally, demonstrating that there was no of outer hair cells in the cochlea, even sub-clinical. Considering the sensitivity of the procedure to detect this type of alteration, it is possible to assume that the lead did not cause cochlear alteration on the structure that was specifically analyzed, finding that corroborates with what is described in the literature 10,11 . were studied; in other words, what would be the lead level to be taken into account in the analyses: the blood lead level at the time of the evaluation, the cumulative level, or another proposal for calculation?…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, the children subjected to evoked otoacoustic emissions through transient stimulus research presented normal result, bilaterally, demonstrating that there was no of outer hair cells in the cochlea, even sub-clinical. Considering the sensitivity of the procedure to detect this type of alteration, it is possible to assume that the lead did not cause cochlear alteration on the structure that was specifically analyzed, finding that corroborates with what is described in the literature 10,11 . were studied; in other words, what would be the lead level to be taken into account in the analyses: the blood lead level at the time of the evaluation, the cumulative level, or another proposal for calculation?…”
Section: Discussionsupporting
confidence: 85%
“…This argumentation is based on a study 11 in which a control group with equivalence on the factors age and level of exposure to noise is used. It found hearing alterations, however there was no difference in the amplitude of the evoked otoacoustic emissions, a product of the distortion between the lead-exposed group associated to noise and the group exposed solely to noise With reference to research done with children, various authors have discussed small changes on the thresholds found on intensities £10dBNA, that is, hearing thresholds that do not clinically represent hearing loss19,20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides medication-related ototoxicity, damage to the hearing apparatus may occur from exposure to other physical agents such as noise, chemicals and heavy metals such as insecticides, toluene, styrene, ethylbenzene, carbon monoxide, carbon disulfide, lead and mercury, among others [2][3][4] . Notwithstanding, the present study will focus on the exposure to medication which are toxic for the human ear and the procedures currently available for the early diagnosis of hearing alterations caused by such exposure.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors offered significant evidence of effects on EOAE results in workers exposed simultaneously to noise and chemicals compared to workers exposed only to noise12 24 28, other authors did not agree23.…”
Section: Resultsmentioning
confidence: 99%